دور رأس المـال الفكـري في عمليّـة تقيـيم الأداء في الجامعــات الحكوميّـة السُّوريّـة - Ghadir, Bassem Ghadir; Mohammad, Laylan Shihap (Latakia University Journal - Economic and Legal Sciences Series, 2019)
دور رأس المـال الفكـري في عمليّـة تقيـيم الأداء في الجامعــات الحكوميّـة السُّوريّـة (دراسـة ميدانيّـة في جامعـة تشريـن) باسم غدير غدير ليلان شهـاب محـمد هدفت هذه الدّراسة إلى تحديـد العلاقة بين رأس المال الفكري وتقييم الأداء في جامعة تشرين؛ من خلال تحديد دور رأس المال الفكري في عمليّـة تقييم الأداء، وقد اعتمد الباحث على كل من المقاربة الاستنباطيَّة كمنهج عــام للبحث والمنهج الوصفي، وقام بتوزيع اسـتبانة على (303) من العاملين في الإدارة المركزيّـة في جامعة تشرين، تمَّ استرداد (274) استبانة، كان صالحاً منها للاستخدام (264) استبانة، ومن ثمَّ أجريت دراسة ميدانيّة بغرض بيان هذه العلاقة، حيث قام الباحث باستخدام معامل ارتباط بيرسون (Pearson Correlation)، وكذلك معامل التّحديد (R Square). توصّل الباحث من خلال الـدّراسة؛ إلى ضعف الاهتمام بالمورد البشري في الجامعة محل البحث، كما يتسم الهيكل التّنظيمي للجامعة بعدم المرونة، بالإضافة إلى قلّة الدّورات التَّدريبيّة للعاملين في مجال الاتصال والتّواصل مع الآخرين، كما أنَّ نظـام ومعايير تقييم الأداء للعاملين في الجامعـة محـل البحث غير واضحة. وقد خلصت الدّراسة إلى وجود علاقة طرديّة معنويّة بين رأس المـال الفكري وتقيـيم الأداء؛ وبالتَّالي وجود دور لرأس المـال الفكري في عمليّة تقييم الأداء في جامعة تشرين؛ كما توصّلت هذه الدّراسة إلى مجموعة من التّوصيات والمقترحات، والَّتي من شأنها أن تسهم بشكلٍ إيجابي بتعزيز دور رأس المـال الفكري في عمليّة تقييم الأداء في الجامعــة محل الدّراسـة. The aim of this study is to identify the Relationship between Intellectual Capital and Performance Evaluation at Tishreen University; By determining the role of Intellectual Capital in the Process of Performance Evaluation. The researcher relied on Both, the Deductive Approach as a general method, and the Descriptive Approach. He distributed a questionnaire to (303) of Employees in the Central Administration at Tishreen University, retrieving (274) Questionnaires, which were valid for use (264) questionnaire, and then conducted a field study for the purpose of this relationship, where the researcher used Pearson Correlation Coefficient, as well as the Coefficient of Selection. The researcher found through the study; There is a lack of interest of the Human Resources at University under study, The Organizational Structure of the University is also inflexible, in addition to the lack of training courses for Communication and Communication staff. The study concluded that; there is a significant relationship between the Intellectual Capital and the Process of Performance Evaluation. Therefore, there is a Role of Intellectual Capital in the Process of Performance Evaluation at Tishreen University. This study also reached a set of recommendations and proposals that would positively contribute to enhancing the Role of Intellectual Capital in the Process of Performance Evaluation at University under study.